Photography Exploration Training using Still Life Techniques for Karmel Tangerang Vocational School Students - Damarjati; Narendra, Yuka Dian (PT FORMOSA CENDEKIA GLOBAL, 2024)
Photography techniques that are supported by equipment that makes it easier for users make this medium increasingly popular with people from all walks of life. Photography has become part of various life activities. Not only selfies, photography has been used in all human activities. Millions of images are produced every day and published on social media pages. This phenomenon aligns that photography has become the property of all society, not just photographers. So the quality of the resulting photos is not just a photograph but can have its own value both in terms of aesthetics and function. For this reason, through training at Karmel Vocational School, it is hoped that it can help hone students' skills so that they can produce photos with the correct techniques so as to produce marketable photographic works with attractive quality. Training with a direct learning method using camera equipment, lighting, object layout, both the background and the objects to be photographed. With this direct learning, it is hoped that students will be able to experiment and explore directly the photo objects they will be photographing. Problems discovered during shooting can be discussed directly to produce maximum photos and provide new knowledge about the techniques of photographing objects/still life.